Preparation of Palm Kernel Shell Binchotan for Radio Frequency Energy Harvesting - Nyimas Febrika Sya'baniah; Nirwan Syarif; Dedi Rohendi; Addy Rachmat; Rio Aldo Syahputra (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Research on the development of radio frequency energy harvesting slabs from palm kernel shells binchotan has been done. The slabs were characterized by using XRD and FTIR intrumentations to determine their crystallography and functional groups. The electrical response of slabs was measured on impedance spectroscopy instrumentation. The conductivity, impedance, and dielectric constant were calculated from impedance spectroscopy data. Diffractograms showed crystalline carbon and confirmed with the existence of peaks, at 2θ, 24.5° and 44.56°. FTIR analysis showed that carbon palm shells have the absorption length is in the range of wave numbers 1100 – 1200 cm-1 for CO of carboxylic acid, aldehyde, ketone and ester, from 1475 to 1600 cm-1 for C=C aromatic ring and double peaks in 1900 – 2100 cm-1 for conjugated C-C. The slabs conductivity varies from 1 to 7 mScm-1. Impedance values for the slabs vary from 1.5 to 2.4 ohm. Dielectric constants for the slabs range from 0.42 to 140.